Medical-Grade Honey Kills Antibiotic-Resistant Bacteria and Prevents Amputation in Diabetics with Infected Ulcers: A Prospective Case Series - Harikrishna K. R. Nair; Nektarios Tatavilis; Ivana Pospíšilová; Jana Kučerová; Niels A. J. Cremers (MDPI AG, 2020)
Diabetic ulcers are at risk of becoming chronic and infected, as diabetics have hampered vascular structures, limiting oxygen and nutrient supply. These wounds can lead to pain, malodor, functional problems, and amputation. The current rise in antibiotic resistance demands for complementary therapies. Medical-grade honey (MGH) forms an attractive option because of its antimicrobial and pro-healing properties. We aim to show the beneficial effects of MGH in infected diabetic ulcers. We present six patients with infected diabetic ulcers, of which some were at risk of (further) amputation. Previous treatments with antibiotics, silver and alginate dressings, surgical closure, and maggot therapy were ineffective; therefore, the treatment was switched to the application of MGH. MGH therapy typically reduced the malodor in a couple of days and controlled infection within 2-3 weeks. MGH also enhanced wound healing by promoting granulation tissue formation, angiogenesis, and re-epithelialization, by decreasing inflammatory and oxidative stress and providing nutrients. Together, wound healing was enhanced, and the patient's quality of life improved. MGH is safe and cost-effective for treating complicated diabetic wounds with (antibiotic-resistant) infections and at risk of amputation. MGH forms a promising alternative or complementary therapy to replace antibiotics for treating locally infected wounds.